Assess participation of Pharmacists among health care staff for Patients with Chronic Diseases - Raed Mohammad Abdullah Alahmadi; Hani Matar DakhiallahAl_Thubaiti; Ammar Naif Almutairy; Abdulrazaq Thurayyan Barak Almutairi; Alaa Rakan Maniullah Albladi; Yousef Owaidh Awdh ALharbi; Khalid Oudah Alahmadi; Abdulrahman Muqpil Alssadi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Chronic diseases are a primary cause of mortality and morbidity globally, necessitating effective, coordinated care among diverse healthcare professionals. In interprofessional teams within hospital settings, each member—particularly pharmacists—contributes unique expertise. Pharmacists’ roles in medication management, patient education, and therapy optimization are vital in managing chronic diseases and enhancing therapeutic outcomes. However, the full scope of pharmacists’ contributions within these teams remains underexplored, especially concerning their impact on patient outcomes, team dynamics, and satisfaction. Methods: A comprehensive literature review was conducted, focusing on studies published in PubMed, Google Scholar, EBSCO, Scopus, and Cochrane Library databases. Search terms included "pharmacist," "interprofessional healthcare," and "chronic disease." Of the initial 340 articles, 17 met the inclusion criteria, discussing aspects of interprofessional healthcare involving pharmacists in chronic disease management, across five dimensions: partnership, coordination, cooperation, shared decision-making, and therapeutic outcomes. Results: Findings indicate that pharmacist involvement significantly enhances interprofessional collaboration, particularly in medication reconciliation, patient education, and monitoring for chronic disease management. Pharmacists’ contributions to interprofessional teams foster shared decision-making and improved therapeutic outcomes, reducing medication errors and supporting adherence to treatment protocols. However, barriers such as resource constraints and role overlaps can hinder effective coordination. Conclusion: Pharmacists play an essential role in chronic disease management within interprofessional teams, improving patient care quality and therapeutic success through enhanced communication and coordination. Further studies are warranted to explore strategies for integrating pharmacists more effectively into team-based chronic disease care, maximizing their role in patient-centered care and long-term health outcomes.